Anthropometric Indices as a Predictive Screening Tool for Hypertension among Young Indian Adults - R. Aruna; Niveatha Santhanakrishnan; Jeneth Berlin Raj (Indian Journal of Public Health)
Background: High blood pressure (BP) is increasing at an alarming rate in India and is the leading cause of cardiovascular disease. Increasing obesity is one of the risk factors for the increasing trend in hypertension among young adults. Objectives: This study aimed to assess the comparative abilities of anthropometric indices of general and central obesity in predicting hypertension among apparently healthy young adults. Materials and Methods: A cross-sectional study was conducted among 493 healthy young adults aged 18 and 25 years. Height, weight, waist, and hip circumference were measured, and anthropometric indices were calculated. BP was measured using an automated BP monitor. Statistical methods such as independent t-test, linear regression, and receiver operating characteristic (ROC) analysis were employed. Results: The prevalence of systolic and diastolic hypertension in males was 15.2% and 17.9%, whereas in females, it was 13% and 14.3%. All anthropometric indices positively correlated with systolic BP and diastolic BP, with the highest being waist circumference (WC). The area under ROC curves (AUC) of the anthropometric indices for predicting hypertension showed that WC had the largest AUCs for systolic and diastolic hypertension, respectively. In males and females, WC had the highest sensitivities of 85.4% and 90.3% for systolic and 84.3% and 88.6% for diastolic hypertension. Conclusion: Anthropometric indices of central adiposity were more significant predictors of hypertension.